Cost-Benefit Analysis of Renewable Energy Adoption in Small and Medium Enterprises (SMEs) in Indonesia - Quoc-Hieu Phan (PT Advanced business journal, 2025)
This study aims to evaluate the economic viability and strategic implications of renewable energy adoption among small and medium enterprises (SMEs) in Indonesia. It addresses the critical gap in tailored cost-benefit analyses for SMEs transitioning to sustainable energy solutions. A mixed-methods approach integrates quantitative financial metrics such as net present value (NPV) and internal rate of return (IRR) with qualitative insights from SME stakeholders. Surveys and interviews were conducted to assess operational savings, investment challenges, and policy impacts. Case studies further illustrate successful adoption models. The results indicate that renewable energy adoption yields substantial operational savings and favorable payback periods, with IRRs averaging above 15%. Social and reputational benefits also drive adoption. However, SMEs face persistent barriers including limited financing, regulatory complexity, and inadequate access to government incentives. The study’s scope is limited to Indonesian SMEs and may not fully generalize across regions or sectors. Future research should expand to include longitudinal data and comparative analyses across ASEAN economies. Policymakers and industry stakeholders are encouraged to develop targeted support mechanisms, including simplified subsidy access and collaborative business models, to facilitate SME engagement in renewable energy transitions. This research offers a comprehensive framework for assessing renewable energy adoption in SMEs, combining financial, social, and policy dimensions. It contributes novel insights into the intersection of sustainability and economic resilience in emerging markets.